Hubungan Riwayat Keluarga, Pola Konsumsi Zat Gizi (Lemak dan Natrium) dan Aktivitas Fisik dengan Kejadian Hipertensi - Kamelia, Raissa; Nurhamidi, Nurhamidi (Journal of Local Therapy, 2023)
Hypertension is a common blood vessel disease suffered by the community, characterized by an increase in systolic blood pressure above 140 mmHg and diastolic blood pressure above 90 mmHg. Objective: This study aimed to found out the correlation between family history, consumption patterns of dietary fat and sodium and physical activity with the incidence of hypertension in the work area of the Lolo Health Center, Paser Regency. Methods: This research is an analytic observational with a cross sectional design. The population is the entire population aged 35-59 years. Samples were taken as many as 48 people with accidental sampling technique. Data collection was collected through interviews with questionnaires. Results: based on the results of the study showed that there was a relationship between family history (p=0.018), dietary fat consumption patterns (p=0.001), physical activity (p=0.003) with the incidence of hypertension, and there was no relationship between consumption patterns of sodium with the incidence of hypertension (p=0.099). Conclusion: respondents are expected to check their blood pressure regularly, limit the consumption of foods that contain high fat and sodium by replacing increased consumption of fruits and vegetables and routinely doing physical activities.